The Role of "Preventive Vaccination in Healthy Children and Children with Chronic Diseases" Discipline in the Specialist Training Curriculum in the Field of "Pediatrics" - Leyla S. Namazova-Baranova; Tatiana E. Privalova; Vilya A. Bulgakova; Yuliya I. Ermakova; Marina V. Fedoseenko; Dina S. Rusinova; Tatiana A. Kalyuzhnaya; Elena A. Vishneva; Firuza Ch. Shakhtakhtinskaya; Maria V. Fominykh (Union of pediatricians of Russia, 2021)
This article presents the experience of teaching the discipline «Preventive Vaccination in Healthy Children and Children with Chronic Diseases». Its significance in preparation of students of pediatric departments of higher educational institutions of Russia is validated. It is shown that the majority of students have positive attitude to vaccination, however, they are not sufficiently informed about the organization of the process itself and they need to obtain such knowledge.